2016
DOI: 10.15267/keses.2016.35.3.288
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Eye-tracking Method in Elementary Science Education Research

Abstract: The purpose of this study is a review of previous studies and principles of eye-tracking techniques that are actively applied in recent elementary science education. Also it proposes to utilize the direction of eye tracking techniques in elementary science education research. Recent eye-tracking technology was developed, using the infrared pupil and the corneal reflection can be safely and accurately track the eye movements of the participants. Eye tracking has the advantage of higher temporal resolution, acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…For example, [58] employed robots to help kids learn multiplication and discovered that their math achievement improved. Similar positive effects have been documented in research involving other grade levels and mathematical disciplines [55,56,57].…”
Section: Ai In Educationsupporting
confidence: 79%
See 1 more Smart Citation
“…For example, [58] employed robots to help kids learn multiplication and discovered that their math achievement improved. Similar positive effects have been documented in research involving other grade levels and mathematical disciplines [55,56,57].…”
Section: Ai In Educationsupporting
confidence: 79%
“…[62] Revealed the extent of using artificial intelligence applications by faculty members in Chinese university education was low. Similarly, [57] showed that the degree of primary school teachers' utilization of AI applications in teaching and application methods in a group of capital schools in Korea was low. [63] Developed an instrument to measure undergraduate students' attitudes toward the ethics of artificial intelligence (AT-EAI), verified its psychometric properties, and evaluated its validity in terms of content and concept.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Artificial intelligence is a path toward the development of students' personalized education, with practical teaching and practical individualization being achievable [7]. Shin and Shin [8] proposed automation, customization, growth, and collaboration as key components of AI-based science education methodologies. Automation refers to AI's ability to continually manage and analyze every pupil's data over a period of time; individualization refers to AI's ability to supply each student with personalized learning recommendations based on their level; and diversity refers to the provision of each student with a unique curriculum and textbook.…”
Section: Literature Review 21 Individualized Instruction and Ai Conve...mentioning
confidence: 99%